A soil conditioner based on increasing the water retention performance of sand ginger black soil and its application method
By fixing nanozeolite adsorbent with zero-valent iron load on the surface of the modified humic acid interpenetrating resin, combined with other components, a soil conditioner was prepared, which solved the problem of poor water retention performance of sand ginger black soil, achieved long-term water absorption and water retention effects, enhanced soil structure and redox characteristics, and effectively reduced cadmium content.
Patent Information
- Application Number
- CN202411906518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The poor water retention performance of sand ginger black soil leads to weak drought resistance and poor structural properties, which affects the water supply capacity of crops and the redox characteristics of the soil, making it difficult to effectively play the role of cadmium reduction.
A soil conditioning agent is prepared by fixing the nano-zeolite adsorbent supported by nano-zeolite loading on the surface of the modified humic acid interpenetrating resin, combining other components such as organic fertilizer and microbial complex bacterial agent to form a water retention agent powder, which improves the water retention and structure of sand ginger black soil.
It achieves long-term water absorption and water retention effects, improves the redox characteristics of the soil, enhances the aerability and water retention of the soil, effectively plays the role of cadmium reduction, and improves the sustained release of fertilizers and the survival rate and activity of microbial complex bacteria agents.
Smart Images

Figure 67A714F70A62E
Abstract
Description
Technical Field
[0001] The invention belongs to the field of soil remediation fertilizers, and particularly relates to a soil conditioner for increasing the water retention performance of sand ginger black soil and an application method thereof. Background Art
[0002] Shajiang black soil is a semi-hydromorphic soil formed by de-swamping of river-lake sediments in a warm temperate semi-humid climate, primarily influenced by local and biological factors. Its profile consists of a black soil layer, a de-swamped layer, and a shajiang layer. Within the 1.5-meter control interval, both the black soil layer and the shajiang layer must coexist, and the thickness of recent, light-colored sediments overlying the black soil layer must be less than 60 cm.
[0003] Sandy black soil has a heavy, sticky texture and poor permeability. Its ability to drain and replenish the soil from the lower layers to the upper layers is poor, making it prone to waterlogging, waterlogging, and drought. These characteristics contribute to its poor drought resistance and are the primary cause of drought susceptibility. Sandy black soil has poor structure and contains a high concentration of sandy black soil, which occupies space within the soil and affects its water-holding capacity. This results in a low water supply capacity and intensity, hindering the timely water supply to crops. Furthermore, capillary water rises slowly and to a low height, hindering crop utilization of groundwater.
[0004] Chinese patent application CN113444529A discloses a soil conditioner for treating heavy metal pollution in cultivated land and its preparation method. The soil conditioner comprises a uniform mixture of zeolite, quicklime, hydroxyapatite, composite algae powder, sodium-modified bentonite, magnesium silicate, potassium sulfoselenide, nano-zero-valent iron, modified molybdenum disulfide, and humic acid resin. However, after the soil conditioner is applied to sand ginger black soil, the soil's poor water retention affects the soil's redox characteristics, making it difficult to fully exert its cadmium-reducing effect. Summary of the Invention
[0005] The purpose of the present invention is to provide a soil conditioner based on increasing the water retention performance of sand ginger black soil and its application method, a nano zeolite adsorbent loaded with nano zero-valent iron is fixed on the surface of a modified humic acid interpenetrating resin to prepare a water-retaining agent powder, and other components are combined to prepare a soil conditioner that helps improve the water retention of sand ginger black soil. After application to the sand ginger black soil, a long-term water retention effect is achieved, which helps to maintain the redox characteristics of the soil and effectively exerts the cadmium reduction effect of the nano zeolite adsorbent.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for applying a soil conditioner for increasing the water retention performance of sand ginger black soil comprises the following steps:
[0008] Spread 1000-2000kg / mu of soil conditioner on the surface of the soil to be treated, then plow and stir the soil to be treated together with the conditioner spread on it 3-4 times according to the plowing and stirring method, with a turning depth of 20-25cm, and sow after 7-10 days.
[0009] The soil conditioner is prepared by the following steps:
[0010] Step 1: Humic acid powder, 1 / 2 of the total amount of acrylic acid solution and deionized water are added to a reactor, nitrogen protection is introduced, and the reaction is stirred at 95-100° C. and 500-600 r / min for 1-2 hours. The reaction is cooled to 55-65° C., sodium sulfite as an initiator, the remaining acrylic acid solution and hydroxymethyl acrylamide as a cross-linking agent are added to the reactor, and the reaction is heated to 70-80° C. and stirred at 500-600 r / min for 3-4 hours. The reaction is filtered, and the filter cake is washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried at 60-80° C. for 1-2 hours to obtain modified humic acid interpenetrating resin powder.
[0011] Step 2: Add a 60-70% mass fraction of NaOH solution, sodium aluminum silicate and sodium silicate into the reactor, stir at 60-70°C and 200-300r / min for 1-2h, cool naturally, mix aluminum sulfate, a 70-80% mass fraction of concentrated sulfuric acid solution and deionized water evenly and add them to the reactor, continue stirring and reacting for 1-2h, seal the resulting mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 90-100°C, statically crystallize for 30-35 hours, wash the crystals with deionized water and anhydrous ethanol 2-3 times respectively, and vacuum dry at 60-80°C for 1-2h to obtain nano zeolite powder.
[0012] Step 3: Add nano zeolite powder, 5-hydroxyisophthalic acid and deionized water to the reactor, dissolve sodium hexadecyl sulfate as a surfactant in a 70-75% mass fraction ethanol aqueous solution and add it to the reactor, stir at 50-60 ° C and 400-500 r / min for 1-2 hours, add zinc sulfate to the reactor, continue stirring and reacting for 1-2 hours, introduce nitrogen protection, and then add ferrous sulfate heptahydrate to the reactor. Add potassium borohydride solution with a mass fraction of 60-70% to the reactor at a rate of 30-40 mL / min. After the addition is complete, continue the reaction for 4-5 hours, filter, and wash the filter cake with deionized water and anhydrous ethanol 2-3 times respectively, and vacuum dry at 60-80 ° C for 16-18 hours to obtain a nano zeolite adsorbent.
[0013] Step 4: Add the modified humic acid interpenetrating resin powder and deionized water into the reactor, heat to 40-50 ° C, stir and react at 500-600 r / min for 40-50 minutes, then add the nano zeolite adsorbent into the reactor, continue stirring and reacting for 2-3 hours, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry at 60-80 ° C for 1-2 hours, and crush to obtain water retaining agent powder.
[0014] Step 5: Add water-retaining agent powder, organic fertilizer, microbial compound agent and crushed corn stalks into a blender and mix them evenly to obtain a soil conditioner based on increasing the water-retaining performance of sand ginger black soil.
[0015] Furthermore, in step 1, the usage ratio of humic acid powder, acrylic acid solution, deionized water, sodium sulfite and hydroxymethyl acrylamide is 4-6 kg: 2-2.4 L: 2-3 L: 1-2 kg: 1-2 kg.
[0016] Furthermore, in step 1, the neutralization degree of the acrylic acid solution is 65-70%, and the concentration of acrylic acid in the acrylic acid solution is 6-7 mol / L.
[0017] Furthermore, in step 2, the usage ratio of NaOH solution, sodium aluminum silicate, sodium silicate, aluminum sulfate, concentrated sulfuric acid solution and deionized water is 1.2-1.5 L: 4-6 kg: 4-5 kg: 1-2 kg: 1-1.2 L: 2-3 L.
[0018] Furthermore, in step 3, the usage ratio of nano zeolite powder, 5-hydroxyisophthalic acid, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, zinc sulfate, ferrous sulfate heptahydrate and potassium borohydride solution is 2-3 kg: 2-3 kg: 2-3 L: 1-1.2 L: 1-2 L: 1-2 kg: 1-1.2 kg: 900-1000 mL.
[0019] Furthermore, in step 4, the usage ratio of the modified humic acid interpenetrating resin powder, deionized water and nano zeolite adsorbent is 3-4 kg: 4-6 L: 3-4 kg.
[0020] Furthermore, in step five, the usage ratio of water-retaining agent powder, organic fertilizer, microbial compound agent and corn straw is 10-15kg: 1-2kg: 1-2kg: 10-15kg.
[0021] Beneficial effects of the present invention:
[0022] 1. The soil conditioner prepared by the present invention has the characteristics of long-term water absorption and water retention, which helps to improve the poor water retention of sand ginger black soil, maintain the redox characteristics of the soil, and effectively play a cadmium-reducing role; improves the soil structure, helps to enhance the aeration of the soil, and makes the soil more loose.
[0023] Soil conditioners contain water-retaining agent powder, organic fertilizer, microbial compound agent and corn straw. Organic fertilizer can improve soil fertility, and microbial compound agent can increase crop disease resistance and yield; corn straw is rich in nitrogen, phosphorus, potassium, calcium, magnesium and other nutrients and organic matter, and is a high-quality source of organic fertilizer.
[0024] 2. The nano-zeolite adsorbent grafted onto the surface of the modified humic acid interpenetrating resin powder exhibits high water absorption capacity, rapid water absorption, strong water retention, and long water retention. Humic acid chemically reacts with minerals in the soil to form stable soil aggregates, thereby improving soil structure and enhancing its aeration, water permeability, and water retention, making the soil more porous. Although humic acid possesses good hydrophilicity, its physical structure, formed by intermolecular forces, is easily destroyed after water absorption. The interpenetrating network structure helps maintain this physical structure, allowing it to better maintain its structure after water absorption, thereby improving its service life and stability.
[0025] 3. The nano-zeolite adsorbent of the present invention has strong ion exchange and adsorption capacity. The nano-zeolite adsorbent adsorbs a large amount of nano-zero-valent iron on its surface, which can undergo redox reaction with heavy metal ions, reducing heavy metal ions to metallic form, and itself is oxidized to Fe 3+ It further combines with heavy metal ions to form solid or dissolved precipitates, thereby effectively removing heavy metal pollution in the soil. The metal skeleton structure generated in situ on the surface of the nano zeolite has a strong adsorption capacity, which can stabilize the nano zero-valent iron and prevent it from agglomerating and oxidizing. It is grafted on the surface of the interpenetrating network structure and evenly dispersed, further isolating oxygen, thereby extending the service life of the nano zero-valent iron; and by grafting on the surface of the interpenetrating network structure, the contact area with heavy metals in the soil is increased, further enhancing the adsorption of heavy metals.
[0026] 4. The water-retaining agent powder of the present invention has a porous, high water absorption and adsorption capacity, and can tightly bind the effective nutrients in the fertilizer and the effective bacteria of the microbial composite agent inside through the pore adsorption force and the electrostatic attraction of anions and cations, further improving the slow release of the fertilizer and reducing nutrient loss. After mixing with the microbial composite agent, it can serve as a carrier material to protect the microbial composite agent from the influence of environmental factors, improve its survival rate and activity, and can slowly release the microbial composite agent, increasing its activity in the soil. Through the immobilization effect of the carrier, the microbial composite agent can better contact with the soil, thereby improving its utilization rate. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0028] Example 1: A soil conditioner for increasing the water retention of sand ginger black soil is prepared by the following steps:
[0029] S1: 4 kg of humic acid powder, 1 L of acrylic acid solution with a neutralization degree of 65% and 2 L of deionized water were added to a reactor, and nitrogen was introduced for protection. The reaction was stirred at 95°C and 500 r / min for 1 hour, and then cooled to 55°C. 1 kg of sodium sulfite as an initiator, 1 L of acrylic acid solution with a neutralization degree of 65% and 1 kg of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 70°C and stirred at 500 r / min for 3 hours. The reaction was filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried in vacuo at 60°C for 1 hour to obtain modified humic acid interpenetrating resin powder.
[0030] Acrylic acid monomers undergo polymerization reaction under the action of initiators to form polyacrylic acid. At the same time, the phenolic hydroxyl groups of humic acid form ester bonds with the carboxyl groups on the polyacrylic acid chain. In addition to chemical bonding, the polymer chains of humic acid and acrylic acid can be physically entangled with each other. This physical entanglement also increases stability and helps to form a uniform, highly water-soluble interpenetrating network structure.
[0031] S2: Add 1.2L of 60% NaOH solution, 4kg of sodium aluminum silicate and 4kg of sodium silicate into the reactor, stir at 60℃ and 200r / min for 1h, cool naturally, mix 1kg of aluminum sulfate, 1L of 70% concentrated sulfuric acid solution and 2L of deionized water, add them into the reactor, continue stirring and react for 1h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 90℃, and statically crystallize for 35h. Wash the crystals twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60℃ for 1h to obtain nano zeolite powder.
[0032] S3: 2 kg of nano zeolite powder, 2 kg of 5-hydroxyisophthalic acid and 2 L of deionized water were added to the reactor, 1 L of sodium hexadecyl sulfate as a surfactant was dissolved in 1 L of 70% ethanol aqueous solution and added to the reactor, stirred at 50 ° C and 400 r / min for 1 hour, 1 kg of zinc sulfate was added to the reactor, and the stirring reaction was continued for 1 hour. Nitrogen protection was introduced, and 1 kg of ferrous sulfate heptahydrate was added to the reactor. 900 mL of 60% potassium borohydride solution was added dropwise to the reactor at a rate of 30 mL / min. After the addition was completed, the reaction was continued for 4 hours, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and vacuum dried at 60 ° C for 16 hours to obtain a nano zeolite adsorbent.
[0033] The surface of the nano-zeolite is rich in (Si-OH), which undergoes esterification reaction with the carboxyl group of 5-hydroxyisophthalic acid, and a metal skeleton is generated in situ on the surface of the nano-zeolite under the action of zinc sulfate and the surfactant sodium hexadecyl sulfate; ferrous sulfate heptahydrate is reduced to nano-zero-valent iron by potassium borohydride in an oxygen-free environment and adsorbed on the nano-zeolite and the metal skeleton.
[0034] S4: Add 3 kg of modified humic acid interpenetrating resin powder and 4 L of deionized water into the reactor, heat to 40 ° C, and stir at 500 r / min for 40 minutes. Then add 3 kg of nano zeolite adsorbent into the reactor, continue stirring and reacting for 2 hours, filter, wash the filter cake with deionized water and anhydrous ethanol twice respectively, dry it in a vacuum at 60 ° C for 1 hour, and crush it to obtain water retaining agent powder.
[0035] The (Si-OH) on the surface of nano-zeolite can chemically bond with the carboxyl group on the surface of the modified humic acid interpenetrating resin powder, so that it is fixed on the resin surface, obtaining a water-retaining agent powder with high water absorption, high adsorption and water retention.
[0036] S5: 10 kg of water-retaining agent powder, 1 g of organic fertilizer, 1 kg of microbial compound agent and 10 kg of crushed corn stalks are added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water-retaining performance of sand ginger black soil.
[0037] Example 2: A soil conditioner for increasing the water retention of sand ginger black soil is prepared by the following steps:
[0038] S1: 5 kg of humic acid powder, 1.1 L of acrylic acid solution with a neutralization degree of 68% and 2.5 L of deionized water were added to a reactor, and nitrogen was introduced for protection. The reaction was stirred at 95 ° C and 500 r / min for 1.5 h, and then cooled to 60 ° C. 1.5 kg of sodium sulfite as an initiator, 1.1 L of acrylic acid solution with a neutralization degree of 68% and 1.1 kg of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 75 ° C and stirred at 550 r / min for 3.5 h. The filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried at 70 ° C for 1.1 h to obtain modified humic acid interpenetrating resin powder.
[0039] S2: Add 1.4L of 65% NaOH solution, 5kg of sodium aluminum silicate and 4.5kg of sodium silicate into the reactor, stir at 65℃ and 250r / min for 1.1h, cool naturally, mix 1.5kg of aluminum sulfate, 1.1L of 75% concentrated sulfuric acid solution and 2.5L of deionized water and add them into the reactor, continue stirring and reacting for 1.1h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 95℃, and statically crystallize for 33h. Wash the crystals with deionized water and anhydrous ethanol three times respectively, and vacuum dry at 68℃ for 1.5h to obtain nano zeolite powder.
[0040] S3: 2.5 kg of nano zeolite powder, 2.5 kg of 5-hydroxyisophthalic acid and 2.5 L of deionized water were added to the reactor, 1.1 L of sodium hexadecyl sulfate as a surfactant was dissolved in 1.5 L of 73% ethanol aqueous solution and added to the reactor, stirred at 55 ° C and 450 r / min for 1.5 hours, 1.5 kg of zinc sulfate was added to the reactor, and the stirring reaction was continued for 1.5 hours. Nitrogen protection was introduced, and 1.1 kg of ferrous sulfate heptahydrate was added to the reactor. 950 mL of 65% potassium borohydride solution was added dropwise to the reactor at a rate of 35 mL / min. After the addition was completed, the reaction was continued for 4.5 hours, filtered, and the filter cake was washed with deionized water and anhydrous ethanol three times respectively, and vacuum dried at 65 ° C for 17 hours to obtain a nano zeolite adsorbent.
[0041] S4: Add 3.5 kg of modified humic acid interpenetrating resin powder and 5 L of deionized water into the reactor, heat to 45 ° C, and stir at 550 r / min for 48 minutes. Then add 3.5 kg of nano zeolite adsorbent into the reactor, continue stirring and reacting for 2.5 hours, filter, wash the filter cake with deionized water and anhydrous ethanol three times respectively, dry it in a vacuum at 68 ° C for 1.5 hours, and crush it to obtain water retaining agent powder.
[0042] S5: 13 kg of water-retaining agent powder, 1.5 kg of organic fertilizer, 1.5 kg of microbial compound agent and 13 kg of crushed corn stalks were added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water-retaining performance of sand ginger black soil.
[0043] Example 3: A soil conditioner for increasing the water retention of sand ginger black soil, prepared by the following method:
[0044] S1: 3 kg of humic acid powder, 600 mL of acrylic acid solution with a neutralization degree of 70% and 3 L of deionized water were added to a reactor, and nitrogen was introduced for protection. The reaction was stirred at 100 ° C and 600 r / min for 2 hours, and then cooled to 65 ° C. 2 kg of sodium sulfite as an initiator, 900 mL of acrylic acid solution with a neutralization degree of 70% and 2 kg of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The mixture was heated to 80 ° C and stirred at 600 r / min for 4 hours. After filtering, the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried at 80 ° C for 2 hours to obtain modified humic acid interpenetrating resin powder.
[0045] S2: Add 900 mL of 70% mass fraction NaOH solution, 4 kcal sodium aluminum silicate and 5 kg of sodium silicate into the reactor, stir at 70 ° C and 300 r / min for 2 hours, cool naturally, mix 2 kg of aluminum sulfate, 600 mL of 80% mass fraction concentrated sulfuric acid solution and 3 L of deionized water, add them to the reactor, continue stirring and reacting for 2 hours, seal the obtained mixed solution in a 5 L polytetrafluoroethylene stainless steel reactor, heat to 100 ° C, and statically crystallize for 35 hours. Wash the crystals with deionized water and anhydrous ethanol three times respectively, and vacuum dry at 80 ° C for 2 hours to obtain nano zeolite powder.
[0046] S3: 3 kg of nano zeolite powder, 3 kg of 5-hydroxyisophthalic acid and 3 L of deionized water were added to the reactor, 1.2 L of sodium hexadecyl sulfate as a surfactant was dissolved in 2 L of 75% ethanol aqueous solution and added to the reactor, stirred at 60 ° C and 500 r / min for 2 hours, 2 kg of zinc sulfate was added to the reactor, and the stirring reaction was continued for 2 hours. Nitrogen protection was introduced, and 900 g of ferrous sulfate heptahydrate was added to the reactor. 600 mL of 70% potassium borohydride solution was added dropwise to the reactor at a rate of 30 mL / min. After the addition was completed, the reaction was continued for 5 hours, filtered, and the filter cake was washed with deionized water and anhydrous ethanol three times respectively, and vacuum dried at 60 ° C for 18 hours to obtain a nano zeolite adsorbent.
[0047] S4: Add 4 kg of modified humic acid interpenetrating resin powder and 6 L of deionized water into a reactor, heat to 50 ° C, and stir at 600 r / min for 50 minutes. Then add 4 kg of nano zeolite adsorbent into the reactor, continue stirring and reacting for 3 hours, filter, wash the filter cake with deionized water and anhydrous ethanol three times respectively, dry in a vacuum at 80 ° C for 2 hours, and crush to obtain water retaining agent powder.
[0048] S5: 15 kg of water-retaining agent powder, 2 kg of organic fertilizer, 2 kg of microbial compound agent and 15 kg of crushed corn stalks are added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water-retaining performance of sand ginger black soil.
[0049] The microorganisms in the microbial compound agent include Bacillus subtilis, Bacillus licheniformis and actinomycetes, with an effective bacterial count ≥ 1 billion / g and organic matter ≥ 50%.
[0050] The present invention also provides a method for applying a soil conditioner for increasing the water retention performance of sand ginger black soil:
[0051] Spread 1000-2000kg / mu of soil conditioner on the surface of the soil to be treated, then plow and stir the soil to be treated together with the conditioner spread on it 3-4 times according to the plowing and stirring method. The plowing depth is 20-25cm, and sowing can be carried out after 7-10 days.
[0052] Comparative Example 1: Commercially available humic acid powder, nano zeolite, nano zero-valent iron, animal feces, microbial composite agent and crushed corn straw were directly added into a blender in a mass ratio of 10:16:1:4:2:10 and mixed evenly to obtain a soil conditioner.
[0053] Comparative Example 2: Based on Example 3, the humic acid powder and the nano-zeolite adsorbent in step S3 were directly mixed in a mass ratio of 1:1 to prepare a soil conditioner powder. The remaining steps remained unchanged.
[0054] Comparative Example 3: Based on Example 3, in step S4, the nano zeolite adsorbent was replaced with the nano zeolite powder of the same mass in step S2, and the other steps remained unchanged to prepare a soil conditioner.
[0055] Comparative Example 4: Based on Example 3, nano zeolite powder and nano zero-valent iron were evenly mixed in a mass ratio of 1:1 to prepare a soil conditioner as a nano zeolite adsorbent. The other steps remained unchanged.
[0056] In the embodiments and comparative examples:
[0057] The model of the polytetrafluoroethylene stainless steel reactor is RNKL-PTFE5L;
[0058] Humic acid powder was purchased from Shanxi Jiayou Humic Acid Technology Co., Ltd.;
[0059] Nano-zero-valent iron was purchased from Shanghai Maoguo Nanotechnology Co., Ltd.;
[0060] Sodium sulfite, sodium aluminum silicate, sodium silicate, ferrous sulfate heptahydrate, zinc sulfate, potassium borohydride, sodium hexadecyl sulfate, and 5-hydroxyisophthalic acid were purchased from Sigma-Aldrich.
[0061] Organic fertilizer, microbial compound agent and corn straw are all commercially available products.
[0062] Performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 3. 1000 kg / mu of soil conditioner was spread on the surface of the soil to be treated, and then the soil to be treated together with the conditioner spread thereon was plowed and stirred three times according to the plowing and stirring method. The plowing depth was 20 cm to obtain different test soil samples.
[0063] 1. Place the test soil sample 6 months after the application of soil conditioner vertically in pure water for 10 hours, with the water level exceeding the top of the test soil sample, so that the test soil sample can fully absorb water until saturated. Then take out different test soil samples, weigh them and place them vertically on a grid. Weigh them every 1.5 hours at room temperature until the mass of the test soil sample no longer changes, that is, it loses water to a constant weight. Record the mass before water absorption and the mass after full water absorption, and calculate the water absorption (water absorption = mass after full water absorption - mass before water absorption) to evaluate the water absorption capacity of the test soil sample after applying different soil conditioners. Record the time when the mass no longer changes for the first time, which is recorded as the water retention time, to evaluate the water absorption and water retention capacity of the test soil sample after applying different soil conditioners. Retest the water absorption and water retention time of the same batch of test soil samples in the 12th month.
[0064] 2. Refer to "Soil Testing Part 4: Determination of Soil Bulk Density" (NY / T1121.4-2006):
[0065] Use a ring cutter to take different test soil samples, ensuring that the ring cutter is full of soil. Weigh the total mass of the ring cutter and wet soil, dry the ring cutter and soil in an oven to constant weight, and then weigh the mass after drying. Calculate the soil bulk density based on the mass of the dried soil and the volume of the ring cutter: bulk density (g / cm³) = (m2-m1) / V × (1-W / 1000). Then, based on the soil bulk density and soil specific gravity, use the formula: soil porosity = (1-soil bulk density / soil specific gravity) × 100% to calculate the soil porosity and evaluate the air permeability and looseness of the soil after applying different soil conditioners.
[0066] m2 is the mass of the cutter ring and wet soil (g); m1 is the mass of the cutter ring (g); V is the volume of the cutter ring (cm³); and W is the soil moisture content (g / kg).
[0067] 3. The cadmium content of different test samples was measured after 6 and 12 months of application of different soil conditioners according to the ISO 10381-4:2003 method, so as to evaluate the migration and transformation of heavy metals in the soil.
[0068] 4. According to the national standard (GB / T23348-2009): The nitrogen release rate of soil conditioners was determined by performing room temperature extraction at 25°C and rapid extraction at 100°C at the same time. The nutrient release rates of different soils were compared by these two methods.
[0069] 5. Take 25g of test soil and 225mL of sterile water to prepare a 1:10 soil suspension. Then, take 1mL from this homogenous solution and add it to 9mL of sterile saline to prepare a 1:100 homogenous solution. Then take 1mL from this homogenous solution and add it to 9mL of sterile saline to prepare a 1:1000 diluted homogenous solution. After Gram staining the soil suspension, make agar slices with a thickness of 2.5mm. Observe and count the number of colonies under an optical microscope at 10×100 times magnification to evaluate the sustained release and protective effects of different soil conditioners on the microbial composite agent.
[0070] The results are shown in Table 1:
[0071] Table 1
[0072]
[0073] As can be seen from Table 1, the water absorption and water retention time of the soil conditioners prepared in Examples 1 to 3 of the present invention are significantly better than those of the comparative example. The nano-zeolite adsorbent grafted onto the surface of the modified humic acid interpenetrating resin powder increases the water absorption and prolongs the water retention time. In addition, the interpenetrating network structure helps maintain the original physical structure of the humic acid, enabling it to better maintain its structure after water absorption, thereby improving its service life and stability.
[0074] The soil bulk density in Examples 1 to 3 is significantly lower than that in the comparative example, but the soil porosity is significantly better than that in the comparative example 1. Humic acid can react chemically with minerals in the soil to form stable soil aggregates, thereby improving the soil structure, helping to enhance the aeration of the soil, and making the soil more loose. The cadmium content in Examples 1 to 3 is significantly lower than that in the comparative examples 1 to 3. The nano-zeolite adsorbent adsorbs a large amount of nano-zero-valent iron on its surface, which can undergo redox reactions with heavy metal ions, reducing the heavy metal ions to metal form, and itself is oxidized to Fe 3+It further combines with heavy metal ions to form solid or dissolved precipitates. The interpenetrating network structure increases the contact area with heavy metals in the soil, further enhancing the adsorption of heavy metals.
[0075] The cadmium content in Comparative Example 4 is lower than that in Comparative Examples 1 to 3 but higher than that in Example 3. This may be because the metal skeleton structure generated in situ on the surface of the nano-zeolite has a strong adsorption capacity, which can stabilize the nano-zero-valent iron and prevent it from agglomerating and oxidizing. It is grafted on the surface of the interpenetrating network structure and evenly dispersed, further isolating it from oxygen, thereby extending the service life of the nano-zero-valent iron.
[0076] The nitrogen release amount in Examples 1 to 3 was significantly lower than that in Comparative Example 1, and the effective bacterial count was significantly better than that in Comparative Example 1. The water-retaining agent powder was prepared, which could tightly bind the effective nutrients in the fertilizer and the effective bacteria of the microbial composite agent inside through the pore adsorption force and the electrostatic attraction of anions and cations, further improving the slow-release property of the fertilizer, protecting the microbial composite agent, improving its survival rate and activity, and allowing the microbial composite agent to be slowly released.
[0077] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0078] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A soil conditioner based on increasing the water retention performance of sand ginger black soil, characterized in that: The components include the following by mass: 10-15 parts of water retaining agent powder, 1-2 parts of organic fertilizer, 1-2 parts of microbial compound agent and 10-15 parts of corn stalk powder; The water-retaining agent powder is prepared by the following steps: Step 1: Add nano zeolite powder, 5-hydroxyisophthalic acid and deionized water to a reactor, then dissolve sodium hexadecyl sulfate in a 70-75wt% ethanol aqueous solution and add the solution to the reactor, stir at 50-60°C and 400-500r / min for 1-2h, then add zinc sulfate and continue stirring to react for 1-2h, add ferrous sulfate heptahydrate to the reactor under nitrogen protection, then drop 60-70wt% potassium borohydride solution to the reactor, continue to react for 4-5h after the dropwise addition is complete, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a nano zeolite adsorbent; Step 2: Add the modified humic acid interpenetrating resin powder and deionized water into a reactor, stir and react at 40-50°C and 500-600r / min for 40-50min, then add the nano zeolite adsorbent into the reactor, continue stirring and reacting for 2-3h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry, and crush to obtain a water retaining agent powder; The nano zeolite powder is prepared by the following steps: Add 60-70wt% NaOH solution, sodium aluminum silicate and sodium silicate into a reactor, stir at 60-70°C and 200-300r / min for 1-2h, cool naturally, mix aluminum sulfate, 70-80wt% concentrated sulfuric acid solution and deionized water evenly and add them into the reactor, continue stirring and reacting for 1-2h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 90-100°C, statically crystallize for 30-35 hours, wash the crystals with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain nano zeolite powder; The modified humic acid interpenetrating resin powder in step 2 is prepared by the following steps: Humic acid powder, 1 / 2 of the total amount of acrylic acid solution and deionized water are added to a reactor, nitrogen protection is introduced, the reaction is carried out at 95-100° C. and 500-600 r / min for 1-2 hours, the reaction is cooled to 55-65° C., sodium sulfite, the remaining acrylic acid solution and hydroxymethyl acrylamide are added to the reactor, the reaction is heated to 70-80° C., the reaction is stirred at 500-600 r / min for 3-4 hours, the reaction is filtered, the filter cake is washed with ionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried to obtain modified humic acid interpenetrating resin powder; the neutralization degree of the acrylic acid solution is 65-70%.
2. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The dosage ratio of the NaOH solution, sodium aluminum silicate, sodium silicate, aluminum sulfate, concentrated sulfuric acid solution and deionized water is 1.2-1.5L: 4-6kg: 4-5kg: 1-2kg: 1-1.2L: 2-3L.
3. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The usage ratio of the humic acid powder, acrylic acid solution, deionized water, sodium sulfite and hydroxymethyl acrylamide is 4-6kg: 2-2.4L: 2-3L: 1-2kg: 1-2kg.
4. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The concentration of acrylic acid in the acrylic acid solution is 6-7 mol / L.
5. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The dosage ratio of the nano zeolite powder, 5-hydroxyisophthalic acid, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, zinc sulfate, ferrous sulfate heptahydrate and potassium borohydride solution in step 1 is 2-3kg: 2-3kg: 2-3L: 1-1.2L: 1-2L: 1-2kg: 1-1.2kg: 900-1000mL.
6. A soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: In step 2, the usage ratio of the modified humic acid interpenetrating resin powder, deionized water and nano zeolite adsorbent is 3-4 kg: 4-6 L: 3-4 kg.
7. The method for applying a soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The steps include: Spread the soil conditioner on the surface of the treated soil at a rate of 1000-2000kg / mu, then plow and stir the treated soil together with the conditioner spread on it 3-4 times with a plowing depth of 20-25cm, and sow after 7-10 days.
Citation Information
Patent Citations
Soil conditioner for treating heavy metal pollution of cultivated land and preparation method thereof
CN113444529A
Humic acid-based composite water retaining agent and preparation method thereof
CN108948293A
Water-retaining compound fertilizer and preparation method thereof
CN112624853A